An experimental study on the role of augmented reality content type in an outdoor site exploration. Issue 1 (2nd January 2019) - Javornik, Ana; Kostopoulou, Efstathia; Rogers, Yvonne; Fatah gen Schieck, Ava; Koutsolampros, Petros; Maria Moutinho, Ana; Julier, Simon
ABSTRACT: Overlaying a building with images from the past can be an engaging way to explore a historic site. However, little is known about what type of content functions well when using augmented reality (AR) in outdoor contexts. This research investigates how different types of AR content – such as text or image – can affect the flow experience as well as other user affective and behavioural responses. We ran an experimental study with 85 participants at a university campus, where three groups used different apps – AR app with overlaid textual information, AR app with overlaid both textual information and images and an app with audio guide – to explore the area's historic and cultural background. The results show that overlaying images in addition to the text was clearly the most successful way of attracting attention and providing stronger flow in comparison to the apps that overlaid only text or delivered audio. However, we also discovered that users occasionally interpreted the overlaid imagery to be cues for something else other than what they were designed to represent. Finally, we discuss how AR content can enlarge otherwise invisible details, depict historic elements and unveil interiors of buildings.